1996
DOI: 10.1007/bf01808155
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis of the oligomerization of O-phospho-serine, aspartic acid, or glutamic acid by cationic micelles

Abstract: Abstract. Treatment of relatively concentrated aqueous solutions of O-phospho-serine (50 mM), aspartic acid (100 mM) or glutamic acid (100 mM) with carbonyldiimidazole leads to the formation of an activated intermediate that oligomerizes efficiently. When the concentration of amino acid is reduced tenfold, few long oligomers can be detected. Positively-charged cetyltrimethyl ammonium bromide micelles concentrate the negatively-charged activated intermediates of the amino acids at their surfaces and catalyze ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 14 publications
0
21
0
2
Order By: Relevance
“…Higher concentrations of amino acids and CDI favor higher yields and P n s. Furthermore, addition of positively charged surfactants, such as cetyl trimethylammonium bromide, also favor polymerization at the expense of hydrolysis when amino acids with negatively charged side chains are used as monomers. [317] Another research group recently reported [335] that anionic surfactants favor higher yields and higher molecular weights, when (isolated) NCAs are polymerized in water. A particularly interesting finding reported by Orgel and co-workers [318][319][320][321][322] concerns the adsorption of negatively charged oligopeptides (derived from Asp, Glu, or phosphorylated Ser) on minerals, such as ilite or hydroxy apatite.…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher concentrations of amino acids and CDI favor higher yields and P n s. Furthermore, addition of positively charged surfactants, such as cetyl trimethylammonium bromide, also favor polymerization at the expense of hydrolysis when amino acids with negatively charged side chains are used as monomers. [317] Another research group recently reported [335] that anionic surfactants favor higher yields and higher molecular weights, when (isolated) NCAs are polymerized in water. A particularly interesting finding reported by Orgel and co-workers [318][319][320][321][322] concerns the adsorption of negatively charged oligopeptides (derived from Asp, Glu, or phosphorylated Ser) on minerals, such as ilite or hydroxy apatite.…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
“…[310] A second series of experiments that contributed to the credibility that NCAs played an important role in the prebiotic evolution of oligo-and polypeptides was contributed by Orgel and co-workers. [304,[316][317][318][319][320][321][322] These authors studied polymerizations of various a-and b-amino acids activated by carbonyl diimidazole (CDI). Several experimental findings suggest that the polymerization process involves the formation of NCAs that play the role of the true monomers (Scheme 37).…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
“…[310] Eine weitere Serie von Versuchen, die dazu beiträgt, eine nennenswerte Rolle der NCAs in der molekularen Evolution glaubhaft zu machen, wurde von Orgel und Mitarbeitern beigesteuert. [304,[316][317][318][319][320][321][322] Diese Forschergruppe untersuchte Polymerisationen von a-und b-Aminosäuren, die mit Carbonyldiimidazol (CDI) aktiviert wurden. Besonders informativ ist die Beobachtung, dass unter Bedingungen, unter denen aAminosäuren Oligopeptide bilden, b-Aminosäuren in Kombination mit CDI keine Oligoamide liefern.…”
Section: Ncas Und Die Hypothese Der Molekularen Evolutionunclassified
“…Ferner zeigte sich, dass Zugabe positiv geladener Tenside (wie Cetyltrimethylammoniumbromid) die Polymerisation auf Kosten der Hydrolyse begünstigte, wenn Aminosäuren mit negativ geladener Seitenkette als Monomere eingesetzt wurden. [317] Eine andere Arbeitsgruppe berichtete, [335] dass auch anionische Tenside die Polymerisation vorgefertigter (zuvor isolierter) NCAs begünstigen. Ein besonders interessanter Befund von Orgel und Mitarbeitern [318][319][320][321][322] ist die Beobachtung, dass negativ geladene Oligopeptide (basierend auf Asp, Glu oder phosphoryliertem Ser) von Mineralien wie Illit und Hydroxyapatit adsorbiert werden.…”
Section: Ncas Und Die Hypothese Der Molekularen Evolutionunclassified
“…2b), with divalent metal ion catalysts as chemical energy sources. Even using high concentrations of activated monomers and metal ion catalysts [45] or of monomers and condensing agents [46], reactions in bulk aqueous medium usually yield low mass products. This is due in part to the hydrolysis of the active species [5,29] and to the incapacity of the hydrophilic reactive molecules (e.g., uracil derivatives) to form structures, such as monomer stacks, that would facilitate polymerization.…”
Section: Homogeneous Aqueous Mediamentioning
confidence: 99%